How We Do It: Adrenal Biopsy and Ablation - Ashraf Thabet; Rita Lahoud; Khalid Shaqdan; Ronald S. Arellano; Raul N. Uppot (The Arab Journal of Interventional Radiology, 2019)
Adrenal lesions represent a heterogeneous group of neoplasms that may be benign or malignant. If imaging fails to exclude a lesion as definitely benign or if molecular profiling is required, percutaneous image-guided biopsy may be indicated. When an adrenal lesion requires surgical resection, some patients are found to be too high at surgical risk or some patients may refuse adrenalectomy. Image-guided percutaneous thermal ablation can be an effective alternative – radiofrequency, microwave, and cryoablation have all been described in literature for the successful treatment of adrenal tumors. In this article, technical and clinical factors that reduce the risk of complications, some unique to the adrenal gland, are discussed.